(untitled) (Bangladesh Medical Journal, 2021)
Caregivers play an important role for the treatment and wellbeing of the psychiatric patients. Constant caregiving role exert stress on the caregiver which is usually handled by them. This cross-sectional study aimed to assess the level of stress and coping status among conveniently selected 171 care givers of major psychiatric patients at National Institute of Mental Health (NIMH), Dhaka. Data was collected by the pre-tested semi-structure questionnaire blended with perceived stress and coping scale through face to face interview. Average coping status was found in most of the (70%) care givers; good coping status was found in more than one fifth (21%) of the caregivers and few (02%) caregivers had poor coping status. Stress and coping status was found (p<0.05) significantly related. This study finds the perceived stress among all the caregivers under study population; where high level of stress were perceived by more than three fourth of the caregivers and moderate to low level of stress were perceived by most of the caregivers. Caregiver-centric interventions, services and programs are recommended to plan and implement so that they should not compromise their caregiving work. Bangladesh Med J. 2020 Jan; 49 (1): 38-44